New Insights into the Mechanism of Antibacterial Action of Synthetic Peptide Mo-CBP3-PepI against Klebsiella pneumoniae - Levi A. C. Branco; Pedro F. N. Souza; Nilton A. S. Neto; Tawanny K. B. Aguiar; Ayrles F. B. Silva; Rômulo F. Carneiro; Celso S. Nagano; Felipe P. Mesquita; Luina B. Lima; Cleverson D. T. Freitas (MDPI AG, 2022)
Klebsiella pneumoniae is a multidrug-resistant opportunistic human pathogen related to various infections. As such, synthetic peptides have emerged as potential alternative molecules. Mo-CBP3-PepI has presented great activity against K. pneumoniae by presenting an MIC50 at a very low concentration (31.25 µg mL−1). Here, fluorescence microscopy and proteomic analysis revealed the alteration in cell membrane permeability, ROS overproduction, and protein profile of K. pneumoniae cells treated with Mo-CBP3-PepI. Mo-CBP3-PepI led to ROS overaccumulation and membrane pore formation in K. pneumoniae cells. Furthermore, the proteomic analysis highlighted changes in essential metabolic pathways. For example, after treatment of K. pneumoniae cells with Mo-CBP3-PepI, a reduction in the abundance of protein related to DNA and protein metabolism, cytoskeleton and cell wall organization, redox metabolism, regulation factors, ribosomal proteins, and resistance to antibiotics was seen. The reduction in proteins involved in vital processes for cell life, such as DNA repair, cell wall turnover, and protein turnover, results in the accumulation of ROS, driving the cell to death. Our findings indicated that Mo-CBP3-PepI might have mechanisms of action against K. pneumoniae cells, mitigating the development of resistance and thus being a potent molecule to be employed in producing new drugs against K. pneumoniae infections.